Arsenic in Peruvian rice cultivated in the major rice growing region of Tumbes river basin - Mondal D. (2020)
Arsenic (As) exposure from surface and groundwater in Peru is being recognised as a potential threat but there are limited studies on As in the food-chain and none on As in Peruvian rice. In this study, we have determined the As content in rice cultivated in the Tumbes river basin located in the northern province of Peru, an area known for extensive rice cultivation. We collected rice and soil samples from agricultural fields, soil was collected using grid sampling technique while rice was collected from the heaps of harvested crop placed across the fields. The average total As concentration in rice was 167.94 ± 71 μg kg−1 (n = 29; range 68.39–345.31 μg kg−1). While the rice As levels were not highly elevated, the As content of few samples (n = 7) greater than 200 μg kg−1 could contribute negatively to human health upon chronic exposure. Average concentration of As in soil was 8.63 ± 7.8 mg kg−1 (n = 30) and soil to grain transfer factor was 0.025 ± 0.018 for 12 matched samples. Compared to our previous pilot study in 2006 (samples collected from the same agricultural fields but not from exact locations) there was a 41% decrease in As soil concentration in this study. Rice samples collected in 2006 (n = 5) had a mean concentration of 420 ± 109 μg kg−1. Our data provides a baseline of rice grain As concentrations in Peruvian province of Tumbes and warrants further studies on factors affecting uptake of As by the rice varieties cultivated in Peru and any potential human health risks. © 2019 Elsevier Ltd